SANKSI HUKUM TERHADAP PELAKU USAHA YANG MELAKUKAN IKLAN MENYESATKAN (PASAL 17 UNDANG-UNDANG No. 8 TAHUN 1999) - Edwin Yuliska (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Advertising is a highly effective promotional tool in influencing consumer decisions. However, not all advertisements are delivered honestly. Misleading advertising practices are common, including advertisements containing false or exaggerated information or concealing important facts, thus harming consumers. In the context of consumer protection, Law Number 8 of 1999 concerning Consumer Protection, specifically Article 17, expressly prohibits misleading advertising practices. This research uses a normative juridical method with a statutory approach based on regulations, doctrine, court decisions, and other legal sources. The results show that misleading advertising takes various forms, such as false information regarding the quality, quantity, use, price, and guarantees of goods and services. Article 17 of the Consumer Protection Law prohibits businesses from distributing advertisements that have the potential to deceive consumers and provides a legal basis for imposing administrative, criminal, and civil sanctions on businesses that violate this law.Keywords: Misleading Advertising, Consumer Protection, Article 17 of the Consumer Protection Law, Legal Sanctions, Business Actors.